Reimagining a Model for International Students’ College Readiness and Transition - Trimpe, Michelle (Journal of International Students, 2022)
Existing literature reveals that international students’ contextual awareness of social networks, academic culture, logistics, and cultural differences impact their college readiness and transition to U.S. higher education institutions. As international students’ experience navigating U.S. institutions differs from domestic students’ experience, college readiness models should reflect the differences between the two populations. This article explores Conley’s (2007) facets of college readiness model and its contextual skills and awareness element related to international students. Additionally, this article identifies the need for higher education institutions to take greater ownership in facilitating international students’ college readiness and transition. By supporting international students’ contextual awareness, colleges and universities can help demystify the hidden curriculum and improve international students’ college readiness and transition.